Conformations of the type-1 lacto-N-biose I unit in protein complex structures - Fushinobu, Shinya (Acta Crystallogr F Struct Biol Commun, 2018)
The lacto-N-biose I (Galβ1–3GlcNAc; LNB) disaccharide is present as a core unit of type-1 blood group antigens of animal glycoconjugates and milk oligosaccharides. Type-1 antigens often serve as cell-surface receptors for infection by pathogens. LNB in human milk oligosaccharides functions as a prebiotic for bifidobacteria and plays a key role in the symbiotic relationship of commensal gut microbes in infants. Protein Data Bank (PDB) entries exhibiting the LNB unit were investigated using the GlycoMapsDB web tool. There are currently 159 β-LNB and nine α-LNB moieties represented in ligands in the database. β-LNB and α-LNB moieties occur in 74 and six PDB entries, respectively, as NCS copies. The protein and enzyme structures are from various organisms including humans (galectins), viruses (haemagglutinin and capsid proteins), a pathogenic fungus, a parasitic nematode and protist, pathogenic bacteria (adhesins) and a symbiotic bacterium (a solute-binding protein of an ABC transporter). The conformations of LNB-containing glycans in enzymes vary significantly according to their mechanism of substrate recognition and catalysis. Analysis of glycosidic bond conformations indicated that the binding modes are significantly different in proteins adapted for modified or unmodified glycans.